PEMAHAMAN DASAR FILM DOKUMENTER TELEVISI - Putra, Dilmai; ilhaq, muhsin (Besaung : Jurnal Seni Desain dan Budaya, 2021)
This paper describes the understanding of the basic elements of making documentary films, as a form of communication media that represents real life delivered through electronic media in the form of audio visuals such as television. The discussion in this paper describes the style and form of the documentary based on Gerzon Ayawaila's opinion written in the Documentary book from idea to production. In addition, it is necessary to consider visual elements in the process of realizing the documentary film, namely videography techniques and editing techniques. Television as a medium of conveying messages in which there is a power that presents the fact that the media can shape what we know about the world and can be the main source of various opinions and ideas. The achievement of maximum results is carried out through a systematic and planned process, so that it will get the form of a quality television program that can provide entertainment and knowledge to the audience.